Resistensi 10 Galur Kacang Tanah Hasil Silangan antara Arachis cardenassii dan A. hypogaea terhadap Infeksi Peanut stripe virus (PStV) - Ahmad Riduan; Sudarsono Sudarsono (Jurnal Perlindungan Tanaman Indonesia, 2004)
One of the pathogen infecting peanut in Indonesia is Peanut stripe virus (PStV,), causing stripe and blotch symptoms on infected peanut leaves. The objectives of this research were to evaluate effects of PStV infection on yield of 10 introgression lines of peanut derived from crossing of Arachis cardenasii and A. hypogaea, and to determine the tolerance of these lines against PStV infection. Peanut plants were grown in polybag containing 10 kg of potting soils and were grown under glasshouse conditions. The experimental unit consisted of four plants grown separately in four containers and for each treatment was replicated four times. Peanut plants were inoculated mechanically with Bogor isolate of PStV at 15 days after planting (dap) and harvested at 95-100 dap. Results of the experiment indicated peanut cv. Gajah belonged to moderate tolerance while Kelinci was sensitive against PStV infection. Introgression line NC-CS11, CS30 and WS4 were grouped as tolerance while NC-CS51, WSl, and WS3 were moderate tolerance. The tolerance lines showed mild mosaic symptoms, did not show reduction of plant height and peanut yield upon inoculation with PStV. Introgresion line NC-CS15, CS20,CS22, and CS50 were sensitive against PStV infection, showed moderate to severe mosaic/blotch symptoms, reduction of plant height and peanut yield due to PStV infection. Among the tolerance and moderate tolerance lines, only NC-CS30 showed higher yield as compared to peanut cv. Gajah or Kelinci. Therefore, this line may be developed further as commercial peanut cultivar or be use as donor germplasm for PStV tolerance mechanisms in peanut breeding.